3(2)-2y=

Simple and best practice solution for 3(2)-2y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2)-2y= equation:


Simplifying
3(2) + -2y = 0

Multiply 3 * 2
6 + -2y = 0

Solving
6 + -2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -2y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -2y = 0 + -6
-2y = 0 + -6

Combine like terms: 0 + -6 = -6
-2y = -6

Divide each side by '-2'.
y = 3

Simplifying
y = 3

See similar equations:

| 3(1)-2y=7 | | 3(0)-2y=7 | | (6x+1)+(5x+8)= | | 3(-1)+2y=7 | | 3(-2)+2y=7 | | 3(1)+2y=10 | | 2(6x+4)=3x+10 | | f(-6)=2x+8 | | 10-6a=-4a+-12 | | 3(-1)+2y=10 | | 4y-6=7y-48 | | 3(-2)+2y= | | 4(3x-1)7-x=-2x+3+9x | | 2(2x+4)=5x+4 | | (8x-3y)+(-8x+3y)=16-16 | | 3z+30=51 | | (10m-30)=28 | | X-10=3(X-10) | | y=-0.08x+4.48 | | 5(3r-5)=9r+17 | | 3(2x-5)(2x-5)-(3x-7)(5-2x)=0 | | 2(3x+4)=2x+3 | | 2x+4y=156 | | 4x+-56=12 | | 3(2)-5y=10 | | 24=k(5) | | 3(13-4x)=7-16x | | 3(2)-5=10 | | 3(1)-5y=10 | | 3(0)-5y=10 | | 10x-345=12 | | 3(-1)-5y=10 |

Equations solver categories